CODE MIXING ANALYSIS ON TEACHER'S AND STUDENTS' CLASSROOM INTERACTION OF ICE BREAKING SESSION - Dyah Ayu Condro Rini; Andi Rustandi (Jurnal Siliwangi: Seri Pendidikan, 2018)
In English learning process forces teacher and students mix language, especially when teacher give instructions to students in ice breaking session. Limited vocabulary and limited expression makes students use two language in deliver their opinion. In this study, the writer addressed three research questions; 1) what types of code-mixing are used by the teacher and students in classroom interaction of ice breaking session?; 2) what are the functions of code mixing used the teacher and students in classroom interaction of ice breaking session?; 3) what are teacher’s perspectives on using code mixing in the classroom interaction of ice breaking session?. The purpose of this study was to find out the types, functions and teacher’s perspective in using code mixing in classroom interaction. The result of this study showed that insertion was realized in 51 (30.4%) clauses, alternation was realized in 33 (19.6%) clauses, and congruent lexicalization was realized in 1 (0.6%) clause. Moreover, the writer found that 5 (2.9%) clauses indicated as quotation, for addressee specification those were 12 (7.1%) clauses. Moreover, 20 (11.9%) clauses as repetition, 7 (4.2%) clauses indicated as interjection. Next, message qualification had 1 (0.6%) clause, and personalization objectification had 4 (2.4%) clauses. The last function is facility of expression, those had 35 (20.8%) clauses. The perceptions of teacher in using code mixing are helping the students in comprehending the material and easing to catch the topic, enhancing learning such introducing new words, helping students to express themselves better, and helping to avoid misunderstandings.